2021
DOI: 10.37190/abb-01766-2020-03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the antibacterial properties of polycaprolactone modified with graphene, bioglass and zinc-doped bioglass

Abstract: Purpose: Innovative biomedical filaments for 3D printing in the form of short and biodegradable composite sticks modified with various additives were used to prepare biomaterials for further nasal implants. As the respiratory tract is considered to be potentially exposed to contamination during the implantation procedure there is a need to modify the implant with an antibacterial additives. The purpose of this work was to analyze the effect of biodegradable polymer – polycaprolactone (PCL) modification with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In order to achieve local and targeted therapeutic effects, antibiotics, drugs or metallic ions can be introduced into the biomaterials used for medical devices [ 83 ]. The incorporation of metallic ions as strontium (Sr) [ 84 ], zinc (Zn) [ 85 , 86 ], magnesium (Mg) [ 87 ], copper (Cu) [ 88 ], silver (Ag) or cobalt (Co) [ 89 ] can improve the physicochemical and biological properties of BG composites. For example, Ag or Mg nanoparticles have a strong inhibitory and bactericidal effect, and Co ions interfere in physiological process such as oxygen transport in blood.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In order to achieve local and targeted therapeutic effects, antibiotics, drugs or metallic ions can be introduced into the biomaterials used for medical devices [ 83 ]. The incorporation of metallic ions as strontium (Sr) [ 84 ], zinc (Zn) [ 85 , 86 ], magnesium (Mg) [ 87 ], copper (Cu) [ 88 ], silver (Ag) or cobalt (Co) [ 89 ] can improve the physicochemical and biological properties of BG composites. For example, Ag or Mg nanoparticles have a strong inhibitory and bactericidal effect, and Co ions interfere in physiological process such as oxygen transport in blood.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The experimental results showed that the addition of a small amount of GP (0.5%) to PCL filaments resulted in a significant increase in antimicrobial activity compared to the pure PCL. This is because the structure of the GP may cause damage to the cell membranes of microbes and thus eliminate them [ 54 ].…”
Section: Synthetic Biodegradable Polymers For Antibacterial Applicationsmentioning
confidence: 99%
“…Colonization or infectious diseases are the most frequent complication in surgeries associated with antimicrobial resistance in hospitals [ 19 ]. Additionally, it is increasingly common to find bacteria resistant to traditional antibiotics giving rise to dangerous public health problem [ 12 ].…”
Section: Introductionmentioning
confidence: 99%